Novel Compound Heterozygous Mutations in CRTAP Cause Rare Autosomal Recessive Osteogenesis Imperfecta - Tang, Yen-An; Wang, Lin-Yen; Chang, Chiao-May; Lee, I-Wen; Tsai, Wen-Hui; Sun, H. Sunny (Frontiers in Genetics, 2020)
Whole exome sequencing (WES) has advantages over the traditional molecular test by screening twenty thousands of genes simultaneously and has become an invaluable tool for genetic diagnosis in clinical practice. Here, we reported a family with a child and a fetus presenting undiagnosed skeletal dysplasia phenotypes, while the parents were asymptomatic. WES was applied to the parents and affected fetus to identify genetic cause of the phenotypes. We identified novel compound heterozygous mutations consisting of single nucleotide variant (SNV) and large deletion in the CRTAP gene (NM_006371.4:c.1153-3C>G/hg19 chr3:g.32398837_34210906del). Genetic alterations of CRTAP are known to cause osteogenesis imperfecta (OI) in an autosomal recessive manner. Further examination of the proband’s elder sibling who was diagnosed as OI after birth found that she shares the inherited compound heterozygous mutations of CRTAP, thus the findings support the disease causing role of CRTAP mutations. Through the in vitro molecular test and in silico analysis, the deleterious effects of the splicing-altering SNV in CRTAP (c.1153-3C>G) on gene product were confirmed. Collectively, our WES-based pathogenic variant discovery pipeline identifies the SNVs and copy number variation to delineate the genetic cause on the proband affected with OI. The data not only extend the knowledge of mutation spectrum in patients with skeletal dysplasia but also demonstrate that WES holds great promise for genetic screening of rare diseases in clinical setting.